Development of a statewide network hub for screening, referral, and enrollment into food as medicine programs across Kentucky - Christa Mayfield; Carolyn Lauckner; Joshua Bush; Ethan Cosson; Lauren Batey; Alison Gustafson; Alison Gustafson (Frontiers in Public Health)
Widespread recognition of food as medicine interventions’ role in reducing food insecurity and improving health outcomes has recently emerged. Several states have released In Lieu of Services, state-approved alternative services that may be offered by managed care organizations in place of covered benefits, or 1,115 Medicaid waivers, which may allow for expanded nutrition services to reduce food insecurity and improve health outcomes. However, there are significant gaps in understanding how to create a statewide system for delivering “healthcare by food” interventions. The University of Kentucky Food as Health Alliance first piloted the development of a statewide hub facilitating referral to, enrollment in, and evaluation of food as medicine programs across two healthcare providers (one urban and one rural). We then used a quasi experimental study design to examine effects on systolic and diastolic blood pressure in a target population of Medicaid eligible individuals aged 18–64 with high blood pressure and/or type 2 diabetes in rural and urban areas. Participant allocation was based on geographic location for each program arm with no control group. This feasibility case study aims to: (1) outline the development of a referral system between healthcare and food as medicine providers; (2) describe gaps in referral and enrollment; (3) summarize lessons learned from a statewide network as a blueprint for other states; and (4) present clinical outcomes across three food as medicine programs. Ninety-two referrals were received from UK HealthCare with 21 enrolled in medically tailored meals and 28 enrolled in a grocery prescription (53% enrollment rate). Thirty-two referrals were received from Appalachian Regional Healthcare with 26 enrolled in meal kits (81% enrollment rate). On average, the reduction in systolic blood pressure was 9.67 mmHg among medically tailored meals participants and 6.89 mmHg among grocery prescription participants. Creating a statewide system to address food insecurity and clinical outcomes requires key support from a host of stakeholders. Policy steps moving forward need to consider funding and infrastructure for screening, referral, enrollment and engagement hubs for improved health outcomes.Clinical trial registrationClinicalTrials.gov, NCT06033664.